2010
DOI: 10.1172/jci39492
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy influences glomerular disease susceptibility and maintains podocyte homeostasis in aging mice

Abstract: Injury and loss of podocytes are leading factors of glomerular disease and renal failure. The postmitotic podocyte is the primary glomerular target for toxic, immune, metabolic, and oxidant stress, but little is known about how this cell type copes with stress. Recently, autophagy has been identified as a major pathway that delivers damaged proteins and organelles to lysosomes in order to maintain cellular homeostasis. Here we report that podocytes exhibit an unusually high level of constitutive autophagy. Pod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
674
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 623 publications
(701 citation statements)
references
References 62 publications
24
674
0
3
Order By: Relevance
“…Electron microscopy images showing typical structures of autophagy (see, for example, Hartleben et al ., 2010 and Kume et al ., 2010) were found in podocytes (Fig. 5A,B) and in PCT epithelial cells (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Electron microscopy images showing typical structures of autophagy (see, for example, Hartleben et al ., 2010 and Kume et al ., 2010) were found in podocytes (Fig. 5A,B) and in PCT epithelial cells (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, our results show a negative correlation between GBM thickness and FS width in our animal model. On the other hand, it has been shown that aging induces expansion of podocyte processes (Wiggins et al ., 2005; Hartleben et al ., 2010), a phenomenon that could result in the reduction of FS width. In our control animals, aging also induced podocyte processes expansion, a phenomenon that was partially prevented by CR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Induced autophagy maintains the amino acid pool inside cells to adapt to starvation while constitutive autophagy has been shown to function as a cell-repair mechanism that is important for long-lived postmitotic cells. [7][8][9][10][11] Defects in autophagy have been associated with neurodegenerative diseases, [12][13][14][15] diabetes, 16,17 lysosomal storage disease 18 and the loss of vision. 19 In addition to macroautophagy, microautophagy and chaperone-mediated autophagy (CMA) have been described.…”
mentioning
confidence: 99%